The Bakunun Oral Tradition in the Construction of Kerinci Cultural Identity in the Modern Era - Fiqi Nurmanda Sari; Nurfadliyati Nurfadliyati (Fakultas Ilmu Budaya Universitas Diponegoro, 2026)
This study examines the Bakunun oral tradition as a cultural heritage of the Kerinci community in Jambi, which is currently in a critical condition due to weak intergenerational transmission and the pressures of modernity. The research problem focuses on the forms, existence, and meanings of the Bakunun tradition within Kerinci society, as well as its role in shaping and sustaining cultural identity, particularly among younger generations. The study aims to describe the practice of Bakunun, analyze its current condition of continuity, and reveal the social and cultural meanings embedded in it within the context of social change. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation. Data analysis was conducted through stages of data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The theoretical framework draws on concepts of oral tradition and cultural identity construction, particularly Stuart Hall’s view of identity as a dynamic and continuously negotiated process. The findings indicate that Bakunun functions not only as a form of entertainment and moral education, but also as a medium for transmitting customary values, religiosity, and Kerinci cultural identity. However, limited regeneration and insufficient institutional support have placed this tradition at risk of extinction, highlighting the urgent need for revitalization strategies involving younger generations and educational institutions.